Analysis of Intrinsic Motivation and Organizational Culture on the Performance of Military Court Employees I-02 Medan - Sarifah Aini Kembaren; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze the effect of intrinsic motivation on the performance behavior of the employees of the Military Court I-02 Medan and analyze organizational culture on the performance of the employees of the Military Court I-02 Medan. The method I use is descriptive qualitative method. The subject of this research by way of interviews. The results showed that intrinsic motivation and organizational culture partially had a positive and significant effect on employee performance at the Military Court I-02 Medan